2019
DOI: 10.1177/2192568219868205
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Patient Satisfaction After Decompression Surgery Without Fusion for Lumbar Spinal Stenosis

Abstract: Study Design: Retrospective cohort study. Objectives: Decompression without fusion is a standard surgical treatment for lumbar spinal stenosis (LSS) with reasonable surgical outcomes. Nevertheless, some studies have reported low patient satisfaction (PS) following decompression surgery. The cause of the discrepancy between reasonable clinical outcomes and PS is unknown; moreover, the factors associated with PS are expected to be complex, and little is known about them. This study aimed to identify satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…To adjust for potential confounders we used gender, age, smoking status and BMI as covariates in the analysis. These variables have been identified as independent predictors for surgical outcomes in previous studies [11,17,35,36]. Other potential predictors suggested i.e., depression, grade of physical activity and observed scoliosis could not be included in the analyses due to the absence of such data in the NORDSTEN cohort.…”
Section: Discussionmentioning
confidence: 99%
“…To adjust for potential confounders we used gender, age, smoking status and BMI as covariates in the analysis. These variables have been identified as independent predictors for surgical outcomes in previous studies [11,17,35,36]. Other potential predictors suggested i.e., depression, grade of physical activity and observed scoliosis could not be included in the analyses due to the absence of such data in the NORDSTEN cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study [11] indicated that preoperative NRS leg pain was the only predictor of patient satisfaction following TLIF, which is analogous to our conclusion : for every 1-point increase in preoperative NRS-leg, the risk of FBSS is reduced by 20%. On the one hand, the operation leads to greater improvement in patients a icted to more severe limb pain and result in increased satisfaction [31]. On the other hand, patients with lower NRS leg pain have more complicated operation willingness than those with higher NRS because of relatively mild neurologic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Ogura [27] and Sigmundsson [28] studied the satisfaction after decompression surgery without fusion for lumbar spinal stenosis. Ogura observed a 75% of satisfaction with a postoperative VAS of 1.6.…”
Section: Discussionmentioning
confidence: 99%